Magnetic-electronic pressure response of ilmenite (FeTiO3) - Sibanda, Wisdom Nkosilathi (My University, 2010)
Polycrystalline powders of synthetic and natural Ilmenite (FeTiO3) assemblages pressurized in a diamond anvil cell have been studied at room temperature using 57Fe Mössbauer spectroscopy to elucidate the magnetic‐electronic properties of different ilmenite samples. Natural ilmenite samples used included an untreated sample derived from the Hillindale mining area in KwaZulu‐Natal, South Africa and a heat treated sample of the Hillindale sample (labeled SLS). Careful attention has been paid to the source‐DAC‐detector arrangement to obtain satisfactory count rates for a good signal‐to‐noise ratio. This has been achieved by using the 80o wide aperture of a Boehler‐Almax diamond anvil cell as the entrance aperture for the 14.4 keV resonant γ‐rays. The Fe3+/Fe2+ ratio in the natural sample (SLS) shows a gradual increase from 0 GPa to 14 GPa the highest pressure reached for that sample. The ratio increases gradually from 0.28 to 0.38 at 14 GPa. The phase abundance of the ferric component, in the synthetic sample as deduced from the theoretical fits from the data increases from 0% to 15% at 18.5 GPa, then decreases at higher pressure. A perovskite high pressure phase initiates at ≈ 18 GPa corresponding to Fe2+ in dodecahedral coordination, and over a wide pressure range coexists in ever increasing abundance with the corundum‐type low‐pressure phase. The relative content of Fe2+ in the perovskite phase increases at the expense of Fe2+ in the lowpressure ilmenite phase. The transition to the perovskite phase is sluggish at room temperature. The trend observed in the abundances of the ferric and ferrous components in the untreated sample is similar to what is seen in the synthetic and SLS sample, in that there is an increase in the abundance of the ferric component and a corresponding decrease in the abundance of the ferrous component. In the relatively low pressure region (up to 4 GPa), the Fe3+/Fe2+ ratio in the untreated natural sample significantly increases and continues to slowly increase in a “plateau” region. The ratio is ≈ 0.10 at 0 GPa and ≈ 0.30 at 15 GPa, the highest pressure reached for the sample. Appreciable asymmetry in the Mössbauer lineshape profile is initiated at low pressure and persists to the highest pressure in all samples. This is more evident in the synthetic sample which has a symmetric doublet at ambient pressure. The asymmetry is perhaps attributed to Fe3+ emerging (i.e. pressure‐induced oxidation). Metal‐metal charge transfer along the c‐axis of the unit cell between face sharing octahedra of Fe2+ and Ti4+ cations may be one, albeit, contentious explanation for this. 57Fe Mössbauer experiments using a pelleted sample of synthetic ilmenite show that the asymmetry features due to pelleting (texturing) and development of Fe3+ (in a diamond anvil cell) in the sample are different as evidenced by the Mössbauer line profile of the spectra.